Pengaruh Gerakan Boikot di Sosial Media dan Religiusitas Terhadap Minat Beli Produk Mcdonald’s Pasca Boikot(Studi pada Generasi Z di Kalimantan Tengah) - Siti Atikah; Mutya Paramita Pratita (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study investigates two main hypotheses: the significant influence of boycott movements on social media and religiosity on McDonald's purchase interest after the boycott. Using a quantitative approach, this study collected data from 120 Generation Z respondents in Central Kalimantan through a questionnaire, using purposive sampling. Data analysis was conducted using a series of statistical methods, including descriptive analysis, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R2).The results of the study indicate that the boycott movement on social media has a negative and significant influence, indicating that the more intense the boycott movement, the lower the consumer purchasing interest. Conversely, religiosity has a positive and significant effect, indicating that higher levels of religiosity correlate with increased purchasing interest. The coefficient of determination (R2) of 0.594 or 59.4% indicates that this model has moderate predictive power, where 59.4% of the variation in purchasing interest is explained by the two independent variables. The remaining 40.6% is influenced by other variables outside the model, such as price, competitor product quality, promotions, recommendations from public figures or peers, and consumer awareness levels.